Cost-effectiveness of food, supplement and environmental interventions to address malnutrition in residential aged care: a systematic review. (5th January 2018) - Hugo, Cherie; Isenring, Elisabeth; Miller, Michelle; Marshall, Skye
Abstract: Background: observational studies have shown that nutritional strategies to manage malnutrition may be cost-effective in aged care; but more robust economic data is needed to support and encourage translation to practice. Therefore, the aim of this systematic review is to compare the cost-effectiveness of implementing nutrition interventions targeting malnutrition in aged care homes versus usual care. Setting: residential aged care homes. Methods: systematic literature review of studies published between January 2000 and August 2017 across 10 electronic databases. Cochrane Risk of Bias tool and GRADE were used to evaluate the quality of the studies. Results: eight included studies (3, 098 studies initially screened) reported on 11 intervention groups, evaluating the effect of modifications to dining environment ( n = 1), supplements ( n = 5) and food-based interventions ( n = 5). Interventions had a low cost of implementation (<£2.30/resident/day) and provided clinical improvement for a range of outcomes including weight, nutritional status and dietary intake. Supplements and food-based interventions further demonstrated a low cost per quality adjusted life year or unit of physical function improvement. GRADE assessment revealed the quality of the body of evidence that introducing malnutrition interventions, whether they be environmental, supplements or food-based, are cost-effective in aged care homes was low. Conclusion: this review suggests supplements and food-based nutrition interventions in the aged care setting are clinically effective, have a low cost of implementation and may be cost-effective at improving clinical outcomes associated with malnutrition. More studies using well-defined frameworks for economic analysis, stronger study designs with improved quality, along with validated malnutrition measures are needed to confirm and increase confidence with these findings.